2013
DOI: 10.1016/j.ijadhadh.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of the impact of humid aging on the strength of industrial adhesive joints

Abstract: This paper aims at investigating the aging of a single lap joint (SLJ) in water at 70 1C. Experimental observations show an important decrease of deformability from 1 day of aging, while initial behaviour is not impacted. Further investigations reveal that the initial crack occurs at the interface near extremities of overlaps at a load depending from aging time. To predict the behaviour of the aged SLJ submitted to tensile loading, it is necessary to know precisely the state of stress in the adhesive layer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
(20 reference statements)
1
22
0
2
Order By: Relevance
“…Small deformations of these adherends impacted negatively the internal pressure in bonds. Furthermore, this FE analysis outcome corresponds to the results reported in [14] and [20], showing great similarities in stress concentrations patterns in adhesive layers.…”
Section: Finite Element Analysis Of Specimens Under Thermal Loadssupporting
confidence: 84%
See 1 more Smart Citation
“…Small deformations of these adherends impacted negatively the internal pressure in bonds. Furthermore, this FE analysis outcome corresponds to the results reported in [14] and [20], showing great similarities in stress concentrations patterns in adhesive layers.…”
Section: Finite Element Analysis Of Specimens Under Thermal Loadssupporting
confidence: 84%
“…Also, apart from the experiments, an accurate analytical model was developed, capable of incorporating temperature effect to the joint strength evaluation. Leger et al in [20] described aging of specimens immersed in water, carried out on aluminum coupons. The authors reported that the initial cracks occurred in the vicinity of adhesive layer vertices and that the center of the joint was hardly reached by water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed on this topic. The effect of ageing, which will lead to progressive degradation of mechanical properties of the adhesive joint, is also an important area of research [130].…”
Section: Modelling Of Adhesive and Polymer Joiningmentioning
confidence: 99%
“…Leger et al [28] estudiaron el envejecimiento, mediante la inmersión en agua a 70°C durante periodos de 1, 5 y 14 días, de probetas a solape simple de acero unidas con epoxi. Los resultados indicaron que se producía una diminución importante de la deformación tras 1 día de envejecimiento, mientras que el comportamiento inicial no se ve afectado.…”
Section: Antecedentes Y Estudio Actual De La Técnicaunclassified
“…Los acrílicos termoestables están formados por dos componentes y consiguen una elevada resistencia a cizalladura para muchos metales y plásticos. Debido a su rápido curado y a su alta resistencia (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), los acrílicos son utilizados en operaciones altamente automatizadas. Los acrílicos modificados tienen una buena resistencia al pelado, al impacto y a cortadura en un intervalo de temperatura entre -100° y 120°C.…”
Section: Acrílicos Modificadosunclassified